Industrial Partnership Development Based on the Link and Match Approach: A Needs Analysis at SMKN 1 Pekat - Suherman; Herullah; Muhammad Fuad; Yati Sunaryah (Walidem Institute and Publishing, 2026)
Objective: This study aims to identify the need for link and match-based industrial partnership development to support SMKN 1 Pekat as an agent of change in local agriculture. Theoretical framework: This study is grounded in the concepts of vocational education, link and match policy, industrial partnership theory, and local economic development theory, which emphasize collaboration between schools and industry to improve the relevance and quality of vocational education. Literature review: Previous studies indicate that effective industrial partnerships contribute significantly to curriculum relevance, teacher competency development, student employability, and the strengthening of local economic potential. However, the success of such partnerships depends on the alignment between school needs and industrial support. Method: This study employed a qualitative descriptive approach using a needs assessment method. Data were collected through questionnaires, interviews, and documentation studies involving 29 respondents consisting of vice principals, heads of expertise concentrations, productive teachers, and other teachers at SMKN 1 Pekat. Data were analyzed descriptively by calculating average scores for each aspect and identifying priority needs for industrial partnership development. Results: The findings reveal that the local agricultural aspect obtained the highest average score (3.87), followed by industrial work culture (3.76), and curriculum and learning (3.66). The most urgent partnership development needs include the modernization of practice facilities, implementation of teacher internship programs in industry, and the development of modern agricultural technology. The results indicate that the school's primary needs extend beyond increasing the number of industrial partners to improving the quality of partnerships that strengthen teacher competencies, modernize learning processes, and optimize the utilization of local agricultural potential. Implications: The study emphasizes the importance of collaborative industry partnerships to strengthen vocational education quality and support sustainable local agricultural development. Novelty: This study offers a local agriculture-based framework for industrial partnership development to strengthen link and match implementation in vocational schools.